1998
DOI: 10.1111/j.1949-8594.1998.tb17424.x
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Science, Mathematics, and Technology in a Discipline‐Based Culture

Abstract: The culture of the middle years of schooling in Western Australia, as in many parts of the world, is predominantly discipline based. This paper focuses on exceptions to this norm by describing examples of integrated teaching of science, mathematics, and technology in seventh‐ to ninth‐grade classrooms. Several different forms of integration were found in the 16 Western Australian schools examined in this study, including thematic approaches, cross‐curricular approaches, technology‐based projects, and local com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 8 publications
(9 reference statements)
1
18
0
2
Order By: Relevance
“…As discussed in the literature review, one key argument in the prolonged discourse of curriculum integration was focused on the sequence of integrated teaching and individual subject knowledge learning. Our preliminary finding in this regard does not favor the radical perspective of curriculum integration, which suggests subjects be abolished (Younge & Gehrke, 1993) but supports arguments that school pupils need to learn subject knowledge and skills before taking integrated tasks (Venville et al, 1998). This finding therefore aligns well with the blended/worldly view of curriculum integration that we adopted in the study.…”
Section: Implications For Future Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…As discussed in the literature review, one key argument in the prolonged discourse of curriculum integration was focused on the sequence of integrated teaching and individual subject knowledge learning. Our preliminary finding in this regard does not favor the radical perspective of curriculum integration, which suggests subjects be abolished (Younge & Gehrke, 1993) but supports arguments that school pupils need to learn subject knowledge and skills before taking integrated tasks (Venville et al, 1998). This finding therefore aligns well with the blended/worldly view of curriculum integration that we adopted in the study.…”
Section: Implications For Future Researchsupporting
confidence: 89%
“…As reported by Hatch (1998), Gardner believed that "robust understandings of important phenomena and concepts depend on the study of disciplines like history, the natural science and mathematics, and the development of capabilities to use the methods and approaches of those disciplines" (p. 19). Similarly, Venville, Wallace, Rennie, and Malone (1998) observed that many science teachers felt that pupils need to learn the basic content in subjects before integrated teaching could proceed.…”
Section: Discourse About Curriculum Integrationmentioning
confidence: 95%
“…Some research that has been undertaken has found that teachers feel irritated when they are required to integrate contents that do not connect naturally with the integrated theme, topic, or project (Venville, Wallace, Rennie, & Malone, 1999). Moreover, working in this way does not require teachers extra time to plan.…”
Section: A Pragmatic Approach To Curriculum Integrationmentioning
confidence: 99%
“…During the past few decades, many educators have become increasingly interested in the connection between science and mathematics instruction (Frykholm & Glasson, ; Hamm, ; Huntley, ; Judson & Sawada, ; Pang & Good, ; Venville, Wallace, Rennie, & Malone, ). Berlin and Lee's () examination of several documents revealed that reform documents such as Science for All Americans (Rutherford & Ahlgren, ) have all recommended the integration of school mathematics and science.…”
Section: Theoretical Framework and Perspectivesmentioning
confidence: 99%